Exercise improves the body function and protects the neuronal injury in Parkinson’s disease rats by activating calpain 1 and kallikrein 6 - Guo, Jing; Yang, Jinsuo; Fu, Jiang; Tripathi, Alok (Folia Neuropathologica, 2022)
Parkinson’s disease (PD) is a neurodegenerative disease, which alters body and cognitive functions. The present study evaluates the effect of exercise on body function and neuronal injury against a 6-hydroxydopamine hydrobromide (6-OHDA) induced PD rat model and postulates a possible molecular mechanism of its action. Parkinson’s disease was induced by administration of (20 µg/5 µl at the rate of 1 µl/min) 6-OHDA and exercise training was given to mice by motorized rodent treadmill for a period of 14 days after the confirmation of PD. Behavioural changes were observed by apomorphine-induced rotation and motor function was assessed using the rotarod apparatus. The effect of exercise was observed on the levelof neurochemicals and the expression of calpain-1 (CAPN1) and kallikrein 6 (KLK6) was estimated in brain tissue of PD rats using western blot assay. A more significant improvement in the motor and cognitive function was observed in the PD + exercise group than in the PD group of rats. Exercise attenuates the altered level of g-aminobutyric acid (GABA), dopamine (DA) and glutamate in brain tissue of PD rats. Intracellular concentration of Ca+ ion was reduced significantly in brain tissue of the PD + exercise group compared to PD rats. Moreover, exercise activates the expression of KLK6 and CAPN1 protein in brain tissue of PD rats. In conclusion, data of the study reveal that exercise protects neuronal injury by reducing intracellular concentration Ca+ ion and activates KLK6 and CAPN1 in brain tissue of PD rats and thereby improves motor and cognitive functions.